Syntactical Errors in Students’ Writing: A case study of multilingual classrooms in India - Devi Hellystia (Universitas Negeri Yogyakarta, 2019)
English is widely used as a tool for academic interaction in multilingual countries like India, however teaching English becomes very challenging particularly writing. Teachers have to face a heterogeneous group of students with a multilingual and multicultural background and they tend to bring their local languages and cultures which may affect their ability in English writing. There is an indication that the students insert patterns in their mother tongues when they are involved in writing activities. This paper deals with the syntactical errors found among multilingual learners from an Engineering college in Bhubaneswar, India. The tests were conducted for the undergraduate students who belonged to the 2nd and 4th semester. Written tests were conducted for 130 students in the form of passage and a written essay. The research finding showed that misordering is the highest error rate committed by students with a total percentage of 48%. It is followed by other findings they are, 24% of misformation, 8,2% of omission, and 20% of addition. Keywords: syntactical error, multilingual classrooms, multicultural